ANALISIS PENDAPAT MUHYUDDIN AL NAWAWI YANG MENGANJURKAN MEMILIH JODOH BERAGAMA ISLAM SERTA DAPAT MENAMPAKKAN PERMAINAN MENARIK - Harahap, Haddad Ulum (El-Ahli : Jurnal Hukum Keluarga Islam, 2024)
Mahyuddin Alnawawi has compiled the book Almajmu' fi Syarhi al Muhazdzdab in twenty volumes. Meanwhile, the book al Muhazdzdzab li Asysyafi'i consists of four volumes compiled by Ibrahim al Syirozy. Al Nawawi's greatness in compiling the book made it famous. However, after reading his opinion regarding men choosing their future wives, they only recommend women who are religious, intelligent and good at making them happy. There are too few criteria for women as potential wives. Even though there are still many shortcomings. In the discussion, the library-style muqaran tahlily method is used. After the changes were made, a conclusion was obtained that Mahyuddin al Nawawi stated that men are circumcised by marrying women who have religious knowledge and are good at following their husband's good tastes, Muslim men are obliged to marry Muslim women and Muslim women are obliged to marry men who are Muslim. Muslims too, it would be better to add criteria for men and women in choosing their soul mate by the Al-Qur'an and hadith